1992
DOI: 10.1083/jcb.117.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Slow axonal transport mechanisms move neurofilaments relentlessly in mouse optic axons.

Abstract: Abstract. Pulse-labeling studies of slow axonal trans-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 54 publications
9
65
1
Order By: Relevance
“…The transport profiles were followed to 135 d after labeling and were interpreted as showing only progressive anterograde movement of the labeled proteins. Subsequent reports of slow axonal transport showed similar profiles demonstrating proximal to distal movement of cytoskeletal proteins (Ochs and Johnson, 1969;Griffin et al, 1978Griffin et al, , 1982Griffin et al, , 1984Lasek et al, 1992). These pulse-labeling experiments did not, however, preclude the existence of a retrograde slow component.…”
Section: Discussionmentioning
confidence: 62%
“…The transport profiles were followed to 135 d after labeling and were interpreted as showing only progressive anterograde movement of the labeled proteins. Subsequent reports of slow axonal transport showed similar profiles demonstrating proximal to distal movement of cytoskeletal proteins (Ochs and Johnson, 1969;Griffin et al, 1978Griffin et al, , 1982Griffin et al, , 1984Lasek et al, 1992). These pulse-labeling experiments did not, however, preclude the existence of a retrograde slow component.…”
Section: Discussionmentioning
confidence: 62%
“…F, Effect of varying k on and k off , keeping the ratio k on /k off constant (0.0013/0.021 Ï­ 0.0619; 10,000 neurofilaments in the activated region). Lasek et al (1992) have argued that some faster-moving cytosolic proteins comigrate with neurofilament proteins by onedimensional SDS-PAGE, giving the appearance of two kinetic states for neurofilaments, when in fact there is only one. Using two-dimensional gels, these authors did not detect a distinct stationary component.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term tracking of neurofilament protein transport in vivo on a time scale of days or weeks using radioisotopic pulse labeling has demonstrated that neurofilaments move slowly along axons in an anterograde direction at average rates of Ïł0.1-3 mm/d (i.e., 0.001-0.03 m/s) (Nixon, 1991;Lasek et al, 1992). In contrast, short-term tracking of single neurofilaments in cultured neurons on a time scale of seconds or minutes using live-cell fluorescence imaging has demonstrated that these cytoskeletal polymers actually move at fast rates, which average Ïł0.4 -0.6 m/s, and that their movements are both bidirectional and intermittent (Roy et al, 2000;Wang et al, 2000;Wang and Brown, 2001;Ackerley et al, 2003;Uchida and Brown, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that phosphorylation alters the proportion of neurofilaments that are undergoing proximodistal transport. Whether most neurofilament organelles are moving (Lasek et al, 1992) or most are stationary has been a controversial issue (for reviews, see Hollenbeck, 1989;Lasek et al, 1992;Ochs and Brimijoin, 1993). Several lines of evidence suggest that there is a substantial stationary cytoskeleton (Nixon and Logvinenko, 1986;Nixon et al, 1987;Hollenbeck, 1989;Nixon and Sihag, 1991), and that phosphorylated neurofilaments are closely associated with the stationary phase (Watson et al, 1989a(Watson et al, , 1991.…”
Section: Effects Of Myelination On Neurojilament Numbermentioning
confidence: 99%